Methodology for the optimal design of an integrated first and second generation ethanol production plant combined with power cogeneration. (August 2016) - Bechara, Rami; Gomez, Adrien; Saint-Antonin, Valérie; Schweitzer, Jean-Marc; Maréchal, François
Graphical abstract: Highlights: Method for optimal design of 1st and 2nd generation ethanol and power plant. Process simulation, integration and evaluation model. Bi-objective multi-variable evolutionary optimization run. Profitability analysis for choosing point under different economic scenarios. Analysis of Pareto curve and characterization of optimal point. Abstract: The application of methodologies for the optimal design of integrated processes has seen increased interest in literature. This article builds on previous works and applies a systematic methodology to an integrated first and second generation ethanol production plant with power cogeneration. The methodology breaks into process simulation, heat integration, thermo-economic evaluation, exergy efficiency vs. capital costs, multi-variable, evolutionary optimization, and process selection via profitability maximization. Optimization generated Pareto solutions with exergy efficiency ranging between 39.2% and 44.4% and capital costs from 210 M$ to 390 M$. The Net Present Value was positive for only two scenarios and for low efficiency, low hydrolysis points. The minimum cellulosic ethanol selling price was sought to obtain a maximum NPV of zero for high efficiency, high hydrolysis alternatives. The obtained optimal configuration presented maximum exergy efficiency, hydrolyzed bagasse fraction, capital costs and ethanol production rate, and minimum cooling water consumption and power production rate.